Phylogenetic relationships and intraspecific diversity of a North Patagonian Fescue: evidence of differentiation and interspecific introgression at peripheral populations - Lopez, Aldana; Azpilicueta, Maria Marta; Lopez, Dardo Ruben; Siffredi, Guillermo Lorenzo; Marchelli, Paula (2018)
Peripheral sites usually offer suboptimal conditions for species with wide distributions, where expression of phenotypic variability and potential interspecific hybridization might be enhanced. The Patagonian steppe, the largest and southernmost dryland ecosystem in South America, is characterized by natural rangelands dominated by grasses. Festuca pallescens is a keystone species with a wide distribution in Patagonia over diverse environments reaching the extreme arid zones in the Somuncura plateau, a biogeographical island. Our aim is to study the phylogenetic relationships among Festuca pallescens populations as well as between this species and the sympatric F. argentina in North Patagonia. We analysed fourteen populations along a west-east transect of about 500 km in North Patagonia with three types of molecular markers: ITS, chloroplast trnL-F and eight nuclear microsatellites. Bayesian inferences, maximum parsimony and maximum likelihood analyses with trnL-F and ITS showed that F. pallescens is related to the Patagonian clade within the Festuca phylogeny. However, the easternmost populations of F. pallescens at Somuncura plateau were highly differentiated from the other populations and clustered with F. argentina (a sympatric species of the Asian-American clade). Principal coordinates analyses and Bayesian clustering performed with nuclear microsatellites as well as morphoanatomical traits, showed an intermediate position of one of these easternmost populations with respect to the two species, suggesting admixture. The high genetic variability observed in these peripheral populations highlight their relevance for conservation and might be indicating the existence of evolutionary processes triggering events of speciation in the Patagonian fescues.